TINJAUAN HUKUM PERAMPASAN HAK KONSUMEN ATAS TRANSPARANSI GALON DAPAT DIGUNAKAN KEMBALI DENGAN RISIKO KESEHATAN AKIBAT PAPARAN BISPHENOL-A (BPA) - Rizka Amaliyah Maghfiroh; Moh. Hudi; Ira Poppy Swara; Triony Elviana Monica Sari (Madani: Jurnal Politik dan Sosial Kemasyarakatan, 2024)
Refillable drinking water is water that meets certain quality standards so that it is safe to consume directly after the refilling process. This water meets the specified health requirements and can be drunk directly, either with or without additional processing. The method used is normative with a conceptual approach that focuses on analyzing available secondary data so that it does not require direct field research. This includes several sources, including: data from statistical centers, legal experts or others. Other secondary materials are journals and research results regarding refillable gallons whose storage is not based on BPOM recommendations. Manufacturers lift gallons in open trucks and directly expose them to sunlight, causing Bisphenol-A (BPA) to leach. Apart from that, if it is linked to the principles of Islamic law, it is contrary to the principles of honesty (shidq), transparency (wuduh) and also the prohibition of fraud (tadlis).